Pedagogical Conditions of Using Information and Communication Technologies during the Training of Future Lawyers - Olha Fedorchuk (Pedagogical Discourse, 2021)
The pedagogical conditions of the organization of the educational process are decisive for the formation of professional and information competence of the future lawyer. It is noted that an important pedagogical condition for the formation of professional and information competence of future professionals is the educational information and educational environment. It promotes the orientation of future jurists to independent, exploratory, research activities, the use of Internet resources, various electronic and printed sources to search and analyze the necessary legal information, provides a rationale for choosing the means to solve the problem, forms information competence through inclusion in the educational process professionally-oriented legal tasks. We present the information and educational environment of the legal as a systemically organized set of educational environment, the subject of the educational process, as well as public authorities and local governments; banks and databases, local and global information networks, book collections of libraries, legal and business information centers, courts, prosecutors, departments of internal affairs, business entities, as well as a set of data transmission tools, information legal resources, interaction protocols, hardware software and methodological support that provide educational activities. Studies have shown that the use of ICT tools as a means of education and professional activity can be effective only if the constant need of future lawyers to use ICT tools for owners and professionals is maintained. With this in mind, we offer ways to form such a need: the development of targeted software for various categories of students; ensuring self-actualization of students' needs in the use of ICT tools; organization of training in various professional and defining subjects with the use of ICT; creating opportunities for future lawyers to develop the ability to accumulate and apply practical experience in the use of ICT in various conditions (for example, during internships and training in business entities, courts, law enforcement agencies, the Legal Clinic); creating comfortable conditions for working in a computerized environment.